(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Education is a human right and essential for realization of all other human rights. It is a basic right which helps the individual to live with human dignity the right to education is a fundamental human rights. Every individual, irrespective of race, gender, nationality, ethnic or social origin, religion or political preference, age or disability, is entitled to a free elementary education. Hence the present study has attempted to find out awareness of right to education among secondary school teachers. The sample of 200 secondary school teachers was taken. A self made questionnaire comprising 34 multiple choice items was used by the investigator. It was found that both Government and Private secondary teachers have equal information regarding RTE, whereas Male school teachers are more aware of RTE than Female secondary school teachers Education is the foundation stone of national development. No nation can develops without education. The function of education is to accelerate the progress and development of nation. Education is the only means which brings about national integration. Educational achievement of a nation is also an indicator of national pride. During the pre-british Indian the indigenous secondary education was imparted in Pathshalas, Gurukuls, Gurudwaras and other religious organization. Education was banned for women and for scheduled classes and poor people. After sometimes Christian missionaries and East Indian Company established a few schools with the purpose of spreading Christianity in India. The first organized step to established planned primary schools of four years duration in India was established when Macaulay presented his famous minutes in 1835 with a view to popularize English education. In 1854 Woods Dispatch laid stress on imparting education atleast upto the primary level to the Indians. Later many commissions and committees were set up like India Education Commission 1882, Government resolution on education policy 1904, Gopal Krishan Gokhales Resolution 1911,Hartog committee 1929, Wardha Scheme 1938 and Sargent report 1944. All of them laid stress on free & compulsory primary education. After independence India adopted Article-45 directive principle of state policy laid down in Indian Constitution. The Article says, The state shall endeavour to provide within a period of ten years from the commencement of the constitution free & compulsory education for all children untill they complete the age 6 to 14 years. Kothari Commission (1964-66) recommended qualitative improvement for the purpose of science education, work experience, vocalization of education and development of social, moral and spiritual values, improvement in methods of teaching curriculum, teacher training etc. were recommended. National Policy on Education (1986) emphasized on two aspects. One on the universal enrollment and universal retention of children upto 14 years of age and another on the substantial improvement in teaching quality of education. In order to improve the education of school, Operation, Blackboard was introduced by National Policy on Education. The programme of action (1986) was laid down, the purpose of Operation Blackboard is to ensure provision of minimum essential facilities in secondary schools, material facilities as learning equipment, use of blackboard implies that there is an urgency in this programme. In India, the desire for compulsory education figured in the writing and speeches of our leader before independence. But for national development and national integration, creation of good citizens, preparation for life, development of character, development of individuality, adaptation to environment and making man civilized. India just implemented the Right to Education on 27rd August (Thursday), 2009 by 86th Constitutional amendent. It says, the state shall provide free and compulsory education to all children the age of 6 to 14 years in such manner as the state may, by law, determine. Today education is considered an important public function and the state is seen as the chief provider of education through the allocation of substantial Budgetry resources and regulating the provision of education. The pre-eminent role of the state in fulfilling the Right To Education is enshrined in 1966 International Covenant on Economic, Social and Cultural rights. With regards to realizing the Right to Education the World Declaration on Education for All states that partnerships between government and non-government organizational, the private sector, local communities, religious groups, and families are necessary. The realization of Right to Education on a national level may be achieved through compulsory education or more specifically free and compulsory primary education as stated in both the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights. So as India is first to made education compulsory and free for all. Formal Education is given to everybody without any discrimination of sex, caste, creed and colour. Education is the powerful tool. which accelerates the process of national growth and development. Moreover, economically and socially marginalized adults and children can left themselves out of miseries of darkness and participate fully as variable assets for their nation only with the help of education. Thus, education is a key towards a successful life. Keeping in view the importance of education, the secondary education in India has been made compulsory through 86th constitutional amendment. Moreover Right to Education has declared as fundamental right by this amendment under Article-emerge as a global leader in achieving the millennium development goal of ensuring that all children complete their secondary education by 2015 as set by UNESCO. The secondary stake holders for providing education are the parents and social authorities and both these entities have to be active: parents, by sending education is supported, thus, it is important that teacher should be aware of Right to Education. If teacher are well aware of Right to Education then only he/she can make the students to enjoy its benefits and motivate them to enroll in education. Moreover, if the teacher is fully awakened about the Right Education only then he/she will not dare to exploit the child.